2017
DOI: 10.1007/s11626-017-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide induces apoptosis in undifferentiated human induced pluripotent stem cells

Abstract: Thalidomide, which was formerly available commercially to control the symptoms of morning sickness, is a strong teratogen that causes fetal abnormalities. However, the mechanism of thalidomide teratogenicity is not fully understood; thalidomide toxicity is not apparent in rodents, and the use of human embryos is ethically and technically untenable. In this study, we designed an experimental system featuring human-induced pluripotent stem cells (hiPSCs) to investigate the effects of thalidomide. These cells exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The average number of CD34+ cells in peripheral blood on collection day was higher in the VCD cohort than in the VTD cohort; however, the difference was not statistically significant. The lower number of CD34+ stem cells can be attributed to the toxic effects of thalidomide on hematopoietic stem cells [27]. To conclude, this study provides further data on VTD safety with respect to stem cell mobilization in comparison with VCD.…”
Section: Resultsmentioning
confidence: 67%
“…The average number of CD34+ cells in peripheral blood on collection day was higher in the VCD cohort than in the VTD cohort; however, the difference was not statistically significant. The lower number of CD34+ stem cells can be attributed to the toxic effects of thalidomide on hematopoietic stem cells [27]. To conclude, this study provides further data on VTD safety with respect to stem cell mobilization in comparison with VCD.…”
Section: Resultsmentioning
confidence: 67%
“…Human pluripotent stem cells have proven useful in investigating the teratogenicity of thalidomide in vitro. Studies on the effect of thalidomide on human pluripotent stem cells (hPSCs) characterized cytotoxicity in undifferentiated hPSCs 19,20 and hPSC-derived mesoderm 21 and functional effects on hPSC-derived mesendoderm 22 and cardiac mesoderm 20 at concentrations above 100 µM. However, these studies demonstrated effects of thalidomide on PSCs or PSC-derived mesoderm in vitro at concentrations >5-fold in excess of the thalidomide clinical Cmax 7 , which raises concern regarding the relevance of these effects to thalidomide teratogenicity.…”
mentioning
confidence: 99%